A survey of cattle production in China - Huai, Q.=700 1 Zhiyong, J.; Zhijie, Ch.
(Fr, Es)
Ilus., ref.
Keywords: GANADO BOVINO; CRUZAMIENTO; MEJORAMIENTO ANIMAL; PRODUCCION LECHERA; PRODUCCION CARNICA; ANIMALES DE TIRO; CHINA; REVISTA MUNDIAL DE ZOOTECNIA